Metformin for endometrial hyperplasia (protocol) - Clement, Naomi; Oliver, Thomas R.W.; Shiwani, Hunain; Sanner, Juliane R.F.; Mulvaney, Caroline A.; Atiomo, William (Wiley, 2016)
To determine the efficacy and safety of metformin in treating women with endometrial hyperplasia